MODEL KURIKULUM PENGEMBANGAN DIRI DI MADRASAH ALIYAH - Saidah, Elbina Mamla (STAI Hubbulwathan Duri, 2015)
KTSP is the operational curriculum systematically arranged and detailed kind of preparation, the preparation of which is carried out by each unit of education at the stage of evaluation. Guidance and Counseling (BK) is one component of the KTSP. The rationale for the implementation of guidance and counseling in Schools / Madrasah, not solely lie in the presence or absence of a legal basis (legislation) or the provisions of the above, but more important is on efforts to facilitate learners hereinafter referred to counseling, to be able develop her potential or achieve development tasks (involving the physical, emotional, intellectual, social, and moral-spiritual). Counseling as an individual who is in the process of developing or being (on becoming). Activity Extracurricular are educational activities outside subjects and counseling services to help the development of learners in accordance with the needs, potentials, talents, and interests through activities specially organized by educators or education personnel are capable and in authority in the school / madrasah. Extracurricular activities at school has long been underway, and is generally in the form of the scouts.